Predictive value of the adjusted Global Anti-Phospholipid Syndrome Score on clinical recurrence in APS patients: a longitudinal study. (23rd August 2022) - Barilaro, Giuseppe; Esteves, Alexandra; Della Rocca, Carlo; Perez-Isidro, Albert; Araujo, Olga; Pires da Rosa, Gilberto; Ruiz-Ortiz, Estibaliz; Tàssies Penella, Dolors; Viñas, Odette; Reverter, Joan Carles; Cervera, Ricard; Espinosa, Gerard
Abstract: Objective: To assess the effect of the average adjusted global APS score (aGAPSS) over time on recurrence of clinical manifestations in APS patients through a retrospective longitudinal study. Material and methods: The study included 200 patients with APS. The aGAPSS was calculated for each patient at baseline and on a yearly basis for either up to 6 years (minimum 3 years) or just before the clinical event in patients who experienced clinical recurrence. The mean score per patient was computed. In patients under vitamin K antagonists (VKA) the percentage of time spent within the therapeutic range (TTR) was calculated. Cox regression analysis was performed to determine the cut-off value of the aGAPSS with the strongest association with clinical recurrence. Results: Higher average aGAPSS values were found in patients who experienced clinical recurrence in comparison to patients who did not [8.81 (95% CI 7.53, 10.08) vs 6.38 (95% CI 5.64, 7.12), P  = 0.001], patients with thrombotic recurrence compared with patients with obstetric recurrence [9.48 (95% CI 8.14, 10.82) vs 4.25 (95% CI 0.85, 7.65), P  = 0.006] and patients with arterial thrombosis compared with patients with venous thrombosis [10.66 (S.D. 5.48) vs 6.63 (S.D. 4.42), P  = 0.01]. aGAPSS values >13 points were associated with the highest risk of recurrence in multivariate analysis [HR = 3.25 (95% CI 1.93, 5.45), P  < 0.0001]. TTR was not statistically different between patients who had thrombosis recurrence and patients who had not. Conclusions: Our data support the role of periodic (annual) monitoring of the aGAPSS score in predicting clinical recurrence in patients with APS.